2013
DOI: 10.1021/jp312642g
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived π-Shape Platinum(II) Diimine Complexes Bearing 7-Benzothiazolylfluoren-2-yl Motif on the Bipyridine and Acetylide Ligands: Admixing π,π* and Charge-Transfer Configurations

Abstract: Two π-shape platinum(II) diimine complexes (1 and 2) bearing 7-benzothiazolylfluoren-2-yl motif on the bipyridine and acetylide ligands were synthesized, and their photophysics and reverse saturable absorption were investigated systematically. Both complexes exhibit lowenergy, broad, and weak 1 MLCT (metal-to-ligand charge transfer)/ 1 LLCT (ligand-to-ligand charge transfer) transitions and intense high-energy bipyridine ligand or acetylide ligand localized 1 π,π* transitions mixed with some 1 MLCT/ 1 LLCT/ 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 74 publications
4
41
0
Order By: Relevance
“…[18,27] In addition to the aforementioned work, Weinstein's group reported a detailed study on the excited state dynamics of a Pt II diimine chloride complex bearing a strong electron-withdrawing naphthaldiimide (NDI) substituent on the diimine ligand. [39] It was found that there is little electronic interaction between the Pt(phen)Cl 2 [14,18,20,23,24,27] In this work, we synthesized a Pt II diimine complex and two cationic Ir III complexes bearing the NDI motif on the diimine (N ∧ N) ligand (complexes 2-4 in Figure 1). Pt II complex 1, which contains the 1,10-phenanthroline ligand, was synthesized to be a reference compound for the Pt II complex 2 in order to better understand the role of NDI in the presence of the BTF acetylide ligands.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[18,27] In addition to the aforementioned work, Weinstein's group reported a detailed study on the excited state dynamics of a Pt II diimine chloride complex bearing a strong electron-withdrawing naphthaldiimide (NDI) substituent on the diimine ligand. [39] It was found that there is little electronic interaction between the Pt(phen)Cl 2 [14,18,20,23,24,27] In this work, we synthesized a Pt II diimine complex and two cationic Ir III complexes bearing the NDI motif on the diimine (N ∧ N) ligand (complexes 2-4 in Figure 1). Pt II complex 1, which contains the 1,10-phenanthroline ligand, was synthesized to be a reference compound for the Pt II complex 2 in order to better understand the role of NDI in the presence of the BTF acetylide ligands.…”
Section: Introductionmentioning
confidence: 97%
“…[32,34] The groups of both Bryce and Schanze reported that incorporation of π-conjugated substituents, such as fluorenyl and 4-ethynyl-N,N-dihexylaniline substituents on the N ∧ N ligand led to a mixture of 3 MLCT (metal-to-ligand charge transfer) and 3 π,π* characters in the lowest triplet excited state (T 1 state) and thus increased the T 1 lifetimes. [17,35] Our group also demonstrated that introducing the benzothiazolylfluorenyl (BTF) substituents to the N ∧ N ligand dramatically increased the T 1 state lifetimes for both Pt II diimine acetylide complexes [23] and heteroleptic Ir III complexes. [18,19,27] However, incorporation of the BTF motif into the C ∧ N ligands in the Ir III complex resulted in a reduced T 1 lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, these beneficial effects were gained without loss in the long excited-state lifetimes, which result from the steric crowding imposed by the 2,3,7,8-tetraalkyl groups [36]. 2,2 -Bipyridine ligands bearing phenylethynyl or 4-substituted-phenylethynyl substituents in the 4,4or 5,5'-positions have been the focus of some attention, see for example [37][38][39][40], although, to the best of our knowledge, the use of related bis(diimine)copper(I) complexes in DSCs has not been explored. We now report the preparation and characterization of ligands 1-4 (Scheme 2), their homoleptic [CuL 2 ][PF 6 ] complexes, and the application of these compounds for the in situ assembly of heteroleptic copper(I) dyes on FTO/TiO 2 photoanodes (FTO = fluorine-doped tin oxide) in DSCs.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we synthesized three new cationic Ir(III) complexes (Ir-1-Ir-3 in Chart 1) with a NI substituent on the 7-position of the fluorenyl group in the C^N ligands. 2,2′-Bipyridine (bpy), 1,10-phenanthroline ( phen) and 5,5′-di-(7-benzothiazolylfluoren-2-yl)-2,2′-bipyridine (BTF-bpy) 41 were selected as the N^N ligand in these complexes, respectively.…”
Section: Introductionmentioning
confidence: 99%